The regulation of interfaith marriages in Islamic legal discourse - Azzam, Leena Salah (AUC Knowledge Fountain, 2015)
This thesis examines the reasons behind the consensus on the prohibition of interfaith marriage (IFM) between Muslim women and Scriptural men in Islam (Scriptuaries or Ahl al-kitāb are people belonging to a religion in which a scripture was revealed as the Torah or Bible). The thesis argues that the consensus behind that prohibition is fundamentally determined by (1) the gendered understanding of the construction of qiwwāmah and (2) the perception of the religious other in Islamic tradition. I argue that these conceptualizations of woman and the religious other in Islamic tradition result in a hierarchical marital relationship that intersects in interfaith marriage regulations between husband and wife and Muslim and Scriptural. First, I construct this argument by examining the three verses governing interfaith marriage regulations in the Qur’an. The three verses are variably read by Islamic legal scholars given that there is no definite textual evidence on whether an interfaith marriage between a Muslim woman and a Scriptural man is prohibited. Islamic legal scholars also resort to other forms of clarification to verify their position. Consequently, I examine how the consensus regarding the prohibition was built by providing a conceptual analysis of its two determinant factors. In marriage, the legal postulate of qiwwāmah is understood to sanction the husband’s authority over his wife. Marriage is also articulated as constituting an element of enslavement (riqq) for the wife in Islamic legal discourse. I argue that nature and scope of Qiwwāmah in marriage changes and shifts in meaning in tafsīr literature. With this also comes the tradition’s position marking the permanent socio-religious superiority of the Muslim community over all others. This position I argue overlooks the Qur’an’s varying and distinctive usage of concepts such as: believer (mu’min), Muslim, polytheist (mushrik), unbeliever (kāfir), and the identification of People of the Book (Ahl al-Kitāb). This thesis examines the discourse on these concepts in authoritative Qur’anic commentaries and Islamic legal discourse. Finally, I present early reformists, neo-traditionalists, and feminists’ perceptions and reading of these concepts, arguing that these readings can lead to an inquiry on how IFM regulations can be re-articulated in Islamic legal discourse.